The treatment experiences of people living with ileostomies: an interpretative phenomenological analysis. (13th June 2016) - Spiers, Johanna; Smith, Jonathan A.; Simpson, Phillip; Nicholls, Adam R.
Abstract: Aims: The aim of this study was to explore treatment and healthcare experiences of people living with ileostomies, so nurses can build on best practice while caring for these patients. Background: Ileostomies, where the small intestine is re‐directed out of a stoma in the abdominal wall so waste is collected using a bag, are used to treat conditions including inflammatory bowel disease. Existing research suggests that although life with a stoma can be challenging, ileostomy patients are largely supported by multi‐disciplinary teams. However, more research is needed to understand the nuances of these relationships and experiences of treatment, with a view to improving clinical care. Design: Participants took part in semi‐structured interviews consisting of open‐ended questions about their experiences of life with an ileostomy and their treatments and time in hospital. Points of interest were followed up. Data were collected between July–December of 2014. Methods: The qualitative method interpretative phenomenological analysis was used to analyse interviews with 21 people living with ileostomies. Findings: We present findings from two clinical themes: Issues around treatment and Relationships with multi‐disciplinary teams. Surgical complications were common and several participants reported concerns about addiction to painkillers. Varying attitudes were found around reversal surgery. Many reported experiencing distressing, dehumanizing care, while some felt supported by excellent healthcare providers. Conclusion: People living with ileostomies have a very mixed experience of multi‐disciplinary teams and treatments and much could be done to support them more fully. For example, more information about ileostomies could be given to patients and more training given to nurses around stomas.